2018
DOI: 10.21608/eajbsg.2018.16310
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Some Plant Extracts against Pathogenic Fungi

Abstract: Soil samples were collected from different localities in Cairo, and were assayed for keratinophilic fungi. Five species of fungi classified in two genera were isolated from Giza zoo (animal cages and parks), hospital, public park, local market, primary school, club, and garbage dumping site. Five plants were chosen to investigate their antifungal activity against five isolated dermatophytes: Microsporum gypseum, Microsporum boullardii, Trichophyton mentagrophytes, Trichophyton terrsetre, and Trichophyton verru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They also stated that pomegranate peel extract showed antifungal efficacy analogous to clotrimazole. Another study found that 80% of pomegranate peel extract showed antifungal activity against dermatophytes, such as Trichophyton mentagrophyte 1, Trichophyton verrucosum, Trichophyton terrestrial, Trichophyton mentagrophytes 2, and Microsporum boullardii (Easa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They also stated that pomegranate peel extract showed antifungal efficacy analogous to clotrimazole. Another study found that 80% of pomegranate peel extract showed antifungal activity against dermatophytes, such as Trichophyton mentagrophyte 1, Trichophyton verrucosum, Trichophyton terrestrial, Trichophyton mentagrophytes 2, and Microsporum boullardii (Easa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among these plants, Garlic extract (Allicin) (Easa et al, 2001Rad et al, 2017), in addition to that Eucalyptus is an aromatic medicinal plant which considered one of the proper choices as antimicrobial agent. The leaf extracts of this plant have many effects as anti-inflammatory, anticancer, antifungal, antiviral and antioxidant (Easa & El-Beih, 2002;Seyyednejad et al, 2014;Saadia et al, 2018;Elsonbaty et al ., 2020). The present study aimed to study the characteristics of the most predominant and pathogenic different microbial organisms causing nosocomial infections and how to control of these infections and reduce them using natural antimicrobials.…”
Section: Introductionmentioning
confidence: 99%